Effectiveness of using humor appeal in health promotion materials: evidence from an experimental study in Japan - Machi Suka; Takashi Shimazaki (BMC, 2023)
Abstract Background Public health professionals have prepared and distributed many messages and materials to convince the public to adopt healthy behaviors or reduce risky behaviors. However, health promotion materials do not always have the desired effect due to a lack of ability to engage target audience. This study examined the effectiveness of humor appeal (i.e. using humor as an advertising technique to attract attention and increase acceptance of the message) in health promotion materials and how to use it effectively. Methods Total 17 printable posters with different frames (loss- vs. gain-framed) × tones (humorous vs. non-humorous) × topics (advance care planning, cancer screening, donor registry, smoking cessation, and physical activity) were created and evaluated for comprehensibility, persuasiveness, and resistance through two web-based surveys. Participants who were Japanese adults aged 25-64 years were randomly assigned one of the posters (200 people each) and asked to rate it. The overall score was calculated as the persuasiveness score (EHPM 2017;22:69) minus the resistance score (EHPM 2022;27:20). Results In the advance care planning case, the highest overall score was found in the gain-framed humorous poster, followed by the loss-framed humorous poster, and the non-humorous poster (p = 0.007). In the other 4 cases, the posters using humorous illustrations received a significantly lower scores than the non-humorous poster(s). Conclusion The use of humor appeal can help improve the acceptability and persuasiveness of the message when dealing with a little-known resistance-prone health topic. Humor appeal will provide an effective hook to direct public attention to what they do not know or care about in public health communication.